2012
DOI: 10.1210/en.2011-2098
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Mineralocorticoid Receptor Signaling Plays a Key Role in Aldosterone-Independent Cardiac Fibrosis

Abstract: Mineralocorticoid receptor (MR) activation promotes the development of cardiac fibrosis and heart failure. Clinical evidence demonstrates that MR antagonism is protective even when plasma aldosterone levels are not increased. We hypothesize that MR activation in macrophages drives the profibrotic phenotype in the heart even when aldosterone levels are not elevated. The aim of the present study was to establish the role of macrophage MR signaling in mediating cardiac tissue remodeling caused by nitric oxide (NO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
78
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 107 publications
(83 citation statements)
references
References 43 publications
4
78
0
1
Order By: Relevance
“…Previously, the MR has been shown to regulate leukocyte adhesion on endothelial cells 5 and to promote a proinflammatory macrophage phenotype 29 ; our data show that the cardiomyocyte MR regulates multiple stages of the DOC/salt inflammatory and fibrotic cardiac responses. The early responses to DOC/salt are suppressed in MR-null cardiomyocytes, which may be translated into a loss of the expanded tissue inflammatory response at 8 weeks and abrogation of tissue fibrosis.…”
Section: Perspectivessupporting
confidence: 57%
“…Previously, the MR has been shown to regulate leukocyte adhesion on endothelial cells 5 and to promote a proinflammatory macrophage phenotype 29 ; our data show that the cardiomyocyte MR regulates multiple stages of the DOC/salt inflammatory and fibrotic cardiac responses. The early responses to DOC/salt are suppressed in MR-null cardiomyocytes, which may be translated into a loss of the expanded tissue inflammatory response at 8 weeks and abrogation of tissue fibrosis.…”
Section: Perspectivessupporting
confidence: 57%
“…In comparison, studies in models of CVD and cerebral ischemia have shown that MyMRKO mice have reduced levels of M1 cytokines and that this can occur with and without a reduction in macrophage numbers. 15,16,19 Notably, some of these in vivo studies and experiments using cultured cells have indicated that a deficiency of MR signaling in macrophages can alter macrophage gene expression toward an M2 alternatively activated phenotype. 15,16 Our PCR analysis of CD11b + macrophages isolated from WT and MyMRKO kidneys at day 15 of disease found no difference in the M1/M2 phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Studies employing deletion of MR from specific cell types in mice suggest macrophage MRs play a key role in modulating macrophage polarization and promoting cardiac hypertrophy, inflammation, and fibrosis (10,11,51,79). Loss of MR in macrophage-MR knockout (KO) mice results in reduction in M1 phenotype and mRNA levels for markers of vascular inflammation (10).…”
Section: Role Of Mtor In Immune Regulationmentioning
confidence: 99%